Empagliflozin for the treatment of type 2 diabetes mellitus: An overview of safety and efficacy based on Phase 3 trials 艾格列净治疗2型糖尿病：基于3期试验的安全性与有效性概述. (18th May 2015) - Dailey, George
Abstract In the treatment of type 2 diabetes mellitus (T2DM), a relatively new class of oral agents inhibits sodium–glucose cotransporter 2 (SGLT2), reducing reabsorption of filtered glucose and increasing urinary glucose excretion. Numerous SGLT2 inhibitors have been approved for the treatment of T2DM in adults, most recently empagliflozin, which was approved in Europe and the US in 2014. The Phase 3 program has enrolled >14 000 patients and has assessed the efficacy and safety of empagliflozin as monotherapy and in combination. These studies have demonstrated improvements in glycemic control, and modest reductions in body weight and blood pressure. Empagliflozin was generally well tolerated, with no increased risk of hypoglycemia versus placebo as monotherapy or as add‐on therapy, except when given with sulfonylurea. The studies showed an increased risk of urinary tract and genital infections with empagliflozin, although most infections were mild to moderate in intensity. Furthermore, small (but clinically insignificant) increases in hematocrit and lipid levels have been observed for empagliflozin. Due to the mode of action of empagliflozin, care should be exercised when treating patients at risk of volume depletion. The risks and benefits must be weighed for each patient, but the data reviewed herein show promise for empagliflozin as a treatment for patients with T2DM.